Non Debt Tax Shield, Struktur Aktiva, Profitabilitas dan Ukuran Perusahaan terhadap Kebijakan Hutang Perusahaan pada Sektor Pertambangan yang Terdaftar di BEI - Melly Pitria Indriani; Yenny Ernitawati; Anisa Sains Kharisma; Maftukhin; Nur Afridah (Journal of Accounting and Finance (JACFIN), 2021)
Maintaining the sustainability of the company can be done by paying attention to the company's financial management. If the company's internal funding sources do not reach its operational costs, the option that can be chosen is to use external funding sources (debt). The purpose of this study is to prove whether there is an effect of non-debt tax shield, asset structure, profitability and firm size on debt policy. Sampling used purposive sampling technique. The analysis technique uses multiple linear regression with the help SPSS. Partially the results determine the non-debt tax shield variable has a negative effect on debt policy. However, the asset structure and profitability variables have a significant positive effect on debt policy and the firm size variable shows no effect on the company's debt policy. Simultaneously, non-debt tax shield, asset structure, profitability and firm size affect the company's debt policy.